A technical-economical approach to promote the water treatment & reuse processes. (10th January 2019) - Capocelli, M.; Prisciandaro, M.; Piemonte, V.; Barba, D.
Abstract: Despite the emergency of water scarcity, the man's choices have always been directed towards the mismanagement of this vital resource; drinking water is far from being a right for everyone and is rather scarce and poorly distributed in many areas of the world. The aim of this work is to set up a water cost evaluation methodology based on the energetic equivalence among all the possible treatment strategies, water sources and water end-uses. An economic incentive is proposed on the basis of the thermodynamic and process analysis of a Wastewater Treatment & Reuse (WWTR) Plant. The analysis extends our previous approach to the whole panorama of the water-cycle related technologies. The energy use intensity of different (in-series) process of a water reuse project has been addressed: from the COD and nutrient removal, to the energy harvesting and to the separation of dissolved ions. The incentive is able to reward the processes having the goal of low energy consumption and low carbon emissions. The methodology has been applied to WWTR projects at different scales. The results showed that it is possible to obtain an acceptable Return of Investment (ROI), even for a low plant productivity (around 200 m 3 /day). Moreover, based on the profitability of the WWTR Project, the calculation of the "true value" of the "water source" has been presented. An acceptable price of waster (as a commodity) is evaluated for both wastewater and seawater by varying the potentiality of the water reclamation plant. This calculation could be implemented to evaluate the economic benefit of public investment as well as to reduce the use of water from non-renewable sources.